Generation of Individual Diversity: A Too Neglected Fundamental Property of Adaptive Immune System - Muraille, Eric (Frontiers in Immunology, 2014)
The fitness gains resulting from development of the adaptive immune system (AIS) during evolution are still the subject of hot debate. A large random repertoire of antigenic receptors is costly to develop and could be the source of autoimmune reactions. And yet, despite their drawbacks, AIS-like systems seem to have been independently acquired in several phyla of metazoans with very different anatomies, longevities and lifestyles. This article is a speculative attempt to explore the selective pressures which favoured this striking convergent evolution. It is well known that the AIS enables an organism to produce a specific immune response against all natural or artificial antigenic structures. However, it is frequently neglected that this response is highly variable among individuals. In practice, each individual possesses a “private” adaptive immune repertoire. This individualisation of immune defences implies that invasion and escape immune mechanisms developed by pathogens will certainly not always be successful as the specific targets and organisation of the immune response are somewhat unpredictable. In a population where individuals display heterogeneous immune responses to infection, the probability that a pathogen is able to infect all individuals could be reduced compared to a homogeneous population. This suggests that the individual diversity of the immune repertoire is not a by-product of the AIS but of its fundamental properties and could be in part responsible for repeated selection and conservation of the AIS during metazoan evolution. The capacity of the AIS to improve the management of cooperative or parasitic symbiotic relationships at the individual level could be a secondary development due to its progressive integration into the innate immune system. This hypothesis constitutes a new scenario for AIS emergence and explains the selection of MHC restriction and MHC diversification.